2017
DOI: 10.1016/j.astropartphys.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

γ-ray telescopes using conversions to e+e pairs: event generators, angular resolution and polarimetry

Abstract: We benchmark various available event generators in Geant4 and EGS5 in the light of ongoing projects for high angular-resolution pairconversion telescopes at low energy. We compare the distributions of key kinematic variables extracted from the geometry of the three final state particles. We validate and use as reference an exact generator using the full 5D differential cross-section of the conversion process. We focus in particular on the effect of the unmeasured recoiling nucleus on the angular resolution. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…7), as shown for example by Yadigaroglu (1997). Recently Gros & Bernard (2017a) has shown that the use of the bisector angle of the lepton pair ((φ + + φ − )/2) leads to a maximization of the obtained experimental value of the polarization asymmetry, and therefore to a better precision of the polarization measurement. The second limitation comes from multiple Coulomb scatterings of the charged tracks, leading to an exponential suppression of the asymmetry factor: A ef f = e −2σ 2 φ × A, with σ φ being the azimuthal angular resolution.…”
Section: Pair Production Polarimetry: Basic Principlesmentioning
confidence: 95%
See 2 more Smart Citations
“…7), as shown for example by Yadigaroglu (1997). Recently Gros & Bernard (2017a) has shown that the use of the bisector angle of the lepton pair ((φ + + φ − )/2) leads to a maximization of the obtained experimental value of the polarization asymmetry, and therefore to a better precision of the polarization measurement. The second limitation comes from multiple Coulomb scatterings of the charged tracks, leading to an exponential suppression of the asymmetry factor: A ef f = e −2σ 2 φ × A, with σ φ being the azimuthal angular resolution.…”
Section: Pair Production Polarimetry: Basic Principlesmentioning
confidence: 95%
“…11. Using this technique Gros & Bernard (2017a) has obtained a value of π/4 for the low energy asymptote for the polarization asymmetry. In the high energy limit A ≈ 1/7, as obtained by Boldyshev & Peresunko (1971).…”
Section: Pair Production Polarimetry: Basic Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the bisector φ +− = (φ + + φ − )/2 of the azimuthal angles of the direction of the electron, φ − , and of the positron, φ + , to be the optimal choice [27]. We demonstrated that with that angle definition, our generator is the only one, to our knowledge, to match the known asymptotic expressions for A at low and at high energies [24].…”
mentioning
confidence: 92%
“…With that tool we determined the (68 % containment) contribution to the single-photon angular resolution due to the fact that the momentum of the recoil nucleus cannot be measured, to be ≈ 1.5 rad[E/1 MeV] −5/4 [23,24]. We obtained the contribution to the single-photon angular resolution due to the single-track angular resolution in the case of an optimal trackingà la Kalman to be ∝ p −3/4 [23,25].…”
mentioning
confidence: 99%